2020
DOI: 10.1589/jpts.32.342
|View full text |Cite
|
Sign up to set email alerts
|

Athletic event-specific characteristics in floating toes during the static standing posture

Abstract: We aimed to determine the cause of floating toe syndrome, along with methods for correction and prevention. [Participants and Methods] We recruited 93 Japanese male students. Participants were grouped, according to primary sport, as Sprinters (SPR), Swimmers (SWM), Gymnasts (GYM), Kendoists (KND) and Controls (CON). Degree of floating toe syndrome was measured according to whether any toe was not in full contact with the ground in a static standing posture-the Floating Toe Point (FTP). Two points were given fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Several studies have indicated that the occurrence of floating toes can be significantly influenced by individual variations and lifestyle choices, including regular use of high-heeled footwear and engaging in prolonged and vigorous physical activities. 62,63 There are limitations in the current stage of research. There are many etiological hypotheses, but most of them lack of high-quality evidence, and there is a lack of review articles that have been agreed by experts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the occurrence of floating toes can be significantly influenced by individual variations and lifestyle choices, including regular use of high-heeled footwear and engaging in prolonged and vigorous physical activities. 62,63 There are limitations in the current stage of research. There are many etiological hypotheses, but most of them lack of high-quality evidence, and there is a lack of review articles that have been agreed by experts.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents the tabulated data for the grade distribution of the participants. Yanagiya et al reported that the position of AP-COP is modulated by engagement in competitive sports 8) . Hence, the eligibility criteria for the present study included children who did not engage in routine athletic activities.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…5 Japan Society for the Promotion of Sciences, Tokyo, Japan. 6 Institute of Life Innovation Studies, Toyo University, Tokyo, Japan. 7 Department of Physical Medicine and Rehabilitation, Tohoku University Graduate School, Sendai, Miyagi, Japan.…”
Section: Fundingmentioning
confidence: 99%
“…Floating toes are a condition and deformity of the toes in which all the toes do not contact the ground while standing [1][2][3][4][5][6][7]. Many functional impairments in floating toes have been previously reported.…”
Section: Introductionmentioning
confidence: 99%